Impact of phase separation of whey proteins/hydroxypropylmethylcellulose mixtures on gelation dynamics and gels properties - Jara, Federico Luis (2010)
This work constitutes a study of the impact of phase separation behaviour on the gels properties of a low viscosity hydroxypropylmethylcellulose and whey protein concentrate (WPC) mixed system. The phase separation was characterized by drawing the limit of thermodynamic compatibility, i.e. binodal curve, at pH 6.5 and room temperature (25°C). Gelling properties were studied under thermodynamic compatibility (WPC 12% (w/w)/E50LV 0.25% (w/w) mixed system) and incompatibility conditions (WPC 12% (w/w)/E50LV 4% (w/w) and WPC 20% (w/w)/E50LV 4% (w/w) mixed systems). Under thermodynamic compatibility the WPC/E50LV mixed system shows gelling parameters similar to WPC. Confocal scanning laser microscopy (CSLM) micrographs showed a regular pattern of microdomains of proteins imbibed into E50LV matrix.Confocal microscopy of WPC/E50LV mixture under thermodynamic incompatibility offered details about the constitution of continuous and non-continuous phase and characteristics of non-continuous phase domains. Related to gelling parameters, the solid character upon heating was reinforced in mixed systems since they reflected the concentrating effect arising from phase separation. On the other hand, the solid character of gels upon cooling correlated with the component constituting the continuous phase, and the gelation temperature was similar to polysaccharide-rich phase predicted gelation temperature.Regarding to textural properties, the presence of the polysaccharide diminished the hardness of the mixed gels inducing less resistance to small and large deformation. WPC 20% (w/w)/E50LV 4% (w/w) mixed gel presented an interesting particulated macrostructure. This result would find application in food design and technology if the E50LV concentration is chosen to finely control the rate and extent of WPC aggregation-gelation-particulation. These results could be used in microparticulation or microencapsulation application of whey proteins.